Comparison of transesterified palm stearin/sunflower oil blends catalyzed by Pseudomonas and Mucor javanicus lipase - Lim, L.P.; Ghazali, H.M.; Lai, O.M.; Chu, B.S. (Wiley, 2001)
Palm stearin and sunflower oil mixtures in three different ratio of 3:7, 5:5 and 7:3 (w/w) were subjected to transesterification catalyzed by immobilized lipases from Pseudomonas and Mucor javanicus in a solvent-free system. The ability of these lipases to alter the physical properties of the fat blends was studied. Slip melting point (SMP), differential scanning calorimetry and X-ray diffraction analyses were used to evaluate the physical properties of the transesterified blends. The percentage of free fatty acids liberated was also determined. Results indicated that the Pseudomonas lipase was catalytically more active than Mucor javanicus lipase as shown by marked changes in the triacylglycerol profile and fatty acids released. Pseudomonas lipase-catalyzed mixtures also showed a bigger drop in SMP and successfully changed the polymorphic form from the dominant β crystal form in control blends to β′ crystal form in the transesterified mixtures.